New records of benthic hydroids (Cnidaria: Hydrozoa) from the coast of Oaxaca, Mexico - Humara-Gil, Karla J.; Cruz-Gómez, Christopher (Zootaxa, 2018)
Hydroids of the Pacific coast of Mexico have been little studied. For the coast of Oaxaca, only five papers provide information on species of the region, with some records included in those publications being questionable. Seven species, Pennaria disticha, Clytia linearis, Clytia cf. gracilis, Obelia dichotoma, Ventromma halecioides, Dynamena crisioides and Tridentata turbinata, were discovered during the study and are reported herein. Of these species, Pennaria disticha and Tridentata turbinata are new records for the Mexican Pacific coast, and Clytia linearis and Ventromma halecioides are new records for Oaxaca. Geographic ranges of other hydroids, recorded in earlier studies, are expanded.